Automated proximity sensing in small vertebrates: design of miniaturized sensor nodes and first field tests in bats. Issue 7 (2nd March 2016) - Ripperger, Simon; Josic, Darija; Hierold, Martin; Koelpin, Alexander; Weigel, Robert; Hartmann, Markus; Page, Rachel; Mayer, Frieder
Abstract: Social evolution has led to a stunning diversity of complex social behavior, in particular in vertebrate taxa. Thorough documentation of social interactions is crucial to study the causes and consequences of sociality in gregarious animals. Wireless digital transceivers represent a promising tool to revolutionize data collection for the study of social interactions in terms of the degree of automation, data quantity, and quality. Unfortunately, devices for automated proximity sensing via direct communication among animal‐borne sensors are usually heavy and do not allow for the investigation of small animal species, which represent the majority of avian and mammalian taxa. We present a lightweight animal‐borne sensor node that is built from commercially available components and uses a sophisticated scheme for energy‐efficient communication, with high sampling rates at relatively low power consumption. We demonstrate the basic functionality of the sensor node under laboratory conditions and its applicability for the study of social interactions among free‐ranging animals. The first field tests were performed on two species of bats in temperate and tropical ecosystems. At <2 g, this sensor node is light enough to observe a broad spectrum of taxa including small vertebrates. Given our specifications, the system was especially sensitive to changes in distance within the short range (up to a distance of 4 m between tags). High spatial resolution at short distances enables the evaluation of interactions among individuals at a fine scale and the investigation of close contacts. This technology opens new avenues of research, allowing detailed investigation of events associated with social contact, such as mating behavior, pathogen transmission, social learning, and resource sharing. Social behavior that is not easily observed becomes observable, for example, in animals living in burrows or in nocturnal animals. A switch from traditional methods to the application of digital transceiver chips in proximity sensing offers numerous advantages in addition to an enormous increase in data quality and quantity. For future applications, the platform allows for the integration of additional sensors that may collect physiological or environmental data. Such information complements social network studies and may allow for a deeper understanding of animal ecology and social behavior. Abstract : We present a light‐weight animal‐borne sensor node for proximity sensing in wild animals. At less than two grams this sensor node is light enough to study a broad spectrum of taxa including small vertebrates. This technology opens new avenues of research, allowing detailed investigation of events associated with social contact, such as pathogen transmission, social learning, and resource sharing. Photograph by Christian Ziegler